Analisis Pembelajaran Student Teams Achievement Divisions untuk Meningkatkan Motivasi Belajar Mahasiswa PGSD Universitas Madako Tolitoli - Jepri Utomo; Burhan Burhan (Journal of Elementary School (JOES), 2021)
This study aims to identify and describe the learning of Student Teams Achievement Divisions to increase learning motivation of elementary school teacher education students at Madako Tolitoli University. The method used is a descriptive survey with a qualitative approach. The results showed that when the Student Teams Achievement Divisions learning was applied, students' motivation to learn was good, and had increased. The percentage increase in student learning motivation from learning meetings 1-2 reaches 77% in the high score range, and from learning meetings 2-3 is higher, reaching 89.3% in the very high score range. In addition, from 1-3 learning meetings the total score of each group has increased. The conclusion of this study is that the application of student teams achievement divisions learning in disaster response education courses can increase the learning motivation of PGSD students at Madako Tolitoli University. Keywords: Student Teams Achievement Divisions, Learning Motivation